Science, Technology and Mathematics Education: A roadmap to Economic growth and Sustainable Development of the developing nations - Onoshakpokaiye, Odiri E; E., Aywiri H. (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
The entire globe is shifting rapidly, so in this fast-paced setting, education is essential for directing and propelling national growth. Education in science, technology, and math stands out in this environment as a beacon that might point the way toward economical and sustainable growth. To succeed in the modern inventive period, one has to be able to extract and apply relevant knowledge, recognize important patterns, and understand the foundations of a range of difficulties. The development of the requisite abilities and knowledge may be aided by science, technology, and math education by highlighting the creation of captivating notions about science, the nature of scientific investigation, and its applications. Science is an approach that focuses on various research methods and tasks related to the development, acquisition, and management of knowledge, skills, aptitudes, and attitudes about the natural factors in the environment. The importance of education, economic growth and sustainability, obstacles to and strategies for achieving economic growth and sustainable development in developing countries, and the connection between STEM education and sustainable economic growth were all examined in this study.